ALGORITHM FOR DETERMINATION OF RELIABILITY INDICATOR OF GAS GENERATOR OF HYDROGEN STORAGE AND SUPPLY SYSTEM: Array - Abramov, Y.; Kryvtsova, V.; Mikhailyuk, A. (Municipal economy of cities. Series: «Economy science», 2021)
An algorithm for determining one of the indicators of reliability of the main element of the hydrogen storage and supply system – a gas generator has been developed. Such an algorithm is an integral part of the general algorithm to ensure the required level of fire safety of hydrogen storage and supply systems. The algorithm involves the implementation of several stages. At the first stage, using the expression for the amplitude-frequency characteristic of the gas generator, the functional dependences for its time constants are obtained. These functional dependencies include the values of the transmission coefficient and amplitude-frequency characteristics, which are determined at three a priori set values of frequency. In the second stage, the amplitude-frequency characteristic of the gas generator is determined. For this purpose, an array of data is used, which characterizes the reaction of the gas generator to the test effect in the form of an abrupt change in the area of its outlet. The amplitude-frequency characteristic of the gas generator is determined numerically, and its parameters are the increase in the pressure in the cavity of the gas generator and the time interval at which this increase is determined. The Kotelnikov-Nyquist-Shannon theorem is used to determine this time interval. At the third stage, the probability of the values of the time constants of the gas generator outside the tolerance zone is determined. For this purpose, models of gas generator time constants and their metrological characteristics are used. In the fourth stage, the probability of failure of the gas generator is determined, for which the information of the previous stage is used. At the last stage, the algorithm for determining the probability of failure of the gas generator of the storage and supply system of hydrogen, which is given in verbal form.